Intravitreal Brolucizumab for Choroidal Neovascularization Associated to Angioid Streaks - Somnath Chakraborty; Jay Umed Sheth (Case Reports in Ophthalmological Medicine)
A 44-year-old-female with angioid streak- (AS-) associated choroidal-neovascularization (CNV) was treated with one dose of intravitreal brolucizumab (IB). At one-month, the patient’s visual acuity (VA) improved from 20/120 to 20/40 with a dry macula on spectral-domain optical-coherence tomography (SD-OCT). After observation, the VA improved further to 20/32 with absence of any fluid on the SD-OCT at three months. No ocular or systemic adverse events were noted. In conclusion, intravitreal brolucizumab (IB) is an efficacious and safe therapeutic option for the management of CNV secondary to AS. Further prospective studies with a larger sample size, varied therapeutic regimens, and longer follow-up period are needed to corroborate our findings.